De geologisk-botaniske Forhold i Forbindelse med Rislev-Fundet - Smith, J. Troels (Kuml, 1961)
The Geological-Botanical Conditions in Connection with the Rislev Find. A preliminary report. When the Rislev find was excavated by lecturer Johs. Ferdinand in the early 1940s, peat cutting in Denmark had reached its peak of activity. The newly-established bog laboratory of the National Museum, which was responsible for investigating such bog finds, was faced with many tasks, only a few of which could be dealt with. Furthermore, the methods for investigating bog sites, which were later to produce important results, were still in the experimental stage. On the basis of present bog-geological knowledge and experience it is regrettable that more extensive investigations were not made at that time. The author had the opportunity of making only a few short visits to the excavations and collecting a single series of pollen samples. However, the pollen analytical investigation of the samples, conducted by Bent Fredskild of the National Museum have given an insight into: 1) The natural conditions at the site when the offerings were laid down, 2) Cultivation and grazing in the vicinity, and 3) the forests of the area. The conditions on and near the place of sacrifice. Two pollen counts 1) (totalling 5,000 grains) from the culture layer indicate the following probable conditions. The place of offering was situated on the shore of a small lake. To the landward side there grew an alder-willow (Alnus glutinosa-Salix sp.) swamp. Towards open water and under increasingly moist conditions there were several vegetation zones. First, in fairly moist soil was a zone of Water Mint (Mentha aquatica), Kingcup (Caltha palustris) and an abundance of Meadow-sweet (Filipendula Ulmaria). Next grew a band of reed (Phragmites communis) and sedges (Carex sp.) along with Buck-bean (Menyanthes trifoliata), Great Reedmace (Typha latifolia), Great Water Dock (Rumex Hydrolapathum), and Water-Plantain (Alisma Plantago-aquatica) in shallow water. In the open water, floating and submerged, aquatic plants such as Yellow Water-lily (Nuphar luteum) and Pondweed (Potamegeton sp.) prevailed. On the place of offering itself there presumably grew Meadow-sweet (Filipendula Ulmaria), which was most abundant, Bittersweet (Solanum dulcamara), and Buckler-fern (Dryopteris sp.). Since these are all high-moisture demanding plants and because pollen preservation in the samples is fairly good we can infer moist conditions at the place of offering. We may further conjecture that the offering place was under water in the winter and accessible only during dry periods in summer. lf the pollen samples above and below the culture layer 1) are compared it is apparent that the forest vegetation was spreading over the area. The pollen percentage of water plants [Pollen sum based on the sum of aquatic and marsh plants and of moisture demanding trees, shrubs and herbs.] fell from 3.4 % directly below the culture layer to 1.0 % above the culture layer. Marsh plants also diminished from 8.3 % to 3.6 %. Conversely, the pollen of land plants favouring moist soil increased from 24 to 31 %, and alder rose from 21 to 30 %. The cause of these vegetation changes is not clear, and it cannot be determined on the available evidence whether it represents natural bog succession or a change to drier climatic conditions. Cultivation and grazing in the area. The pollen evidence indicates that the upland vegetation around the offering place was quite open: cultivated and fallow fields and pastures left little room for small woods and groves. A calculation shows that trees and shrubs contributed one-fifth at most of the pollen rain on the offering place. [Pollen sum based on trees and shrubs and open vegetation types exclusive of alder and willow, water plants, marsh plants and plants requiring moist soil.] Pollen of Ribwort (Plantago lanceolata), Mugwort or Field southernwood (Artemesia sp.) and White Clover (Trifolium repens) as well as great quantities of grass (Gramineae) pollen testify to extended pastures, while pollen of cereals, chiefly Rye (Secale cereale) indicates cultivated fields. When in addition the samples above and below the culture layer are considered, two separate and possibly complementary trends in land use are indicated. One concerns the diminishing of grazing land and the other an increase in cultivation. The fluctuations in grass, Plantago lanceolata, Artemisia, and cereal pollen are instructive. Grass pollen, which dominates the spectra below the culture layer, decreases above, while the opposite is true of Plantago and Artemisia pollen. Plantago however, increases only slightly above the culture layer while the Artemisia increases further. Also, cereal pollen shows a steady increase from 0.7 % below to 1.0 % in, and 2.7 % above the culture layer. While it is difficult to interpret these fluctuations, the following sequence of events seems reasonable. First, before the lowest sample was deposited, an extensive clearing of the forest took place possibly in connection with cultivation of grain. The fields then turned into pastures and were grazed for a considerable length of time. Finally, as the uppermost pollen spectra indicates, the area began to revert to forest again. As for the increase in cereal pollen taken together with the decrease of pasture plants there may be several explanations. It is possible that there was a shift from extensive to limited cattle keeping along with a greater emphasis on cultivation. It is also possible that the fields were merely moved closer to the sampling site and pastures cleared farther away. The evidence is far from conclusive and other interpretations may be equally likely. The forests of the area. As was mentioned the woods and thickets contributed less than one-fifth of the pollen rain on the sampling site. These woods were probably not remnants of the primeval forest, but were the secondary growth. Of the forest trees oak (Quercus sp.) dominated, representing 50 % of all tree and shrub pollen (except those types growing on moist soil). Beech (Fagus silvatica) was next important with a pollen percentage of 15 %. Other trees occurring with pollen percentages of less than 10 % are elm (Ulmus sp.), Small-leaved Lime (Tilia cordata), ash (Fraxinis excelsior), hornbeam (Carpinus betulus), aspen (Populus tremula), birch (Betula sp.), and pine (Pinus silvestris). It is characteristic for the relatively open nature of the woods that hazel (Corylus Avellana), buckthorn (Rhamnus cathartica), Guelder Rose (Viburnum Opulus) and Elder (Sambucus nigra) occur. One gets the impression through the pollen analysis that, while the forest was cleared for grazing and grain fields, the woods that grew up also made their contribution to the cultural needs of the inhabitants. In addition to the timber used for construction and tools, acorns and nuts from beech and oak for the swine, and leaf fodder from elm and ash for the cattle were also probably used. There are several indications of a warmer climate than at present. A few grains (5) of yew (Taxus baccata) were found. (This warmth-demanding oceanic plant is rare in Denmark today). In addition mild winters are indicated by the occurance of honeysuckle (Lonicera perclymenum) and ivy (Hedera helix) pollen. The vegetational changes in the small woods reflected in the pollen spectra were not great. Oak pollen increased from 38 % in the lowest sample to 56 % in the culture layer, and then declined somewhat in the sample above. [Pollen sum based on trees and shrubs and open vegetation types exclusive of alder and willow, water plants, marsh plants and plants requiring moist soil.] The opposite is the case with beech, which occurred with 20 % below, 10 % in, and 16 % above the culture layer. Overall these changes indicate that the forests were once more spreading over the area, for the pollen of forest trees increased 12 % over pollen of open plant types. It appears that when the former pastures were reverting to forest, conditions were most favourable for oak to expand. Conclusions. The find can be dated to about 300-400 A.D. by means of the clay vessel which was found at the offering place. This agrees with the fact that rye, whose pollen is common in the samples, was introduced into Denmark around the beginning of the Christian Era. Furthermore no trace of pollen of cornflower (Centaurea Cyanus) was found. This plant did not spread widely in Denmark until the early Middle Ages. The author wishes again to express his indebtedness to Museum inspector Bent Fredskild who conducted the pollen analyses, thus laying the groundwork for this discussion. Samples etc. are kept at the Natura! Sciences Department of the National Museum (Journal No. NM VIII A 3979). ]. Troels-Smith